ANALISIS RANTAI PASOK DAN NILAI TAMBAH AGROINDUSTRI KELANTING DI DESA GANTIMULYO KECAMATAN PEKALONGAN LAMPUNG TIMUR - Aprilia, Muhammad, Nanda; Affandi, Muhammad Irfan; Kasymir, Eka (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to analyze supply chain performanc, and added value in kelanting agroindustry in Gantimulyo Village. This research was conducted at six kelanting agroindustries in Gantimulyo Village, Pekalongan District, East Lampung Regency. Data collection was conducted in February 2019. Data were analyzed using qualitative and quantitative descriptive analysis. Performance measurements were made by comparing indicators on FoodSCOR Card indicators. The calculation of added value used Hayami added value method. The results showed the flow pattern of supply chain started from farmers and agent as the main suppliers of raw materials. The perfomance of kelanting agroindustri showed that the average indicators were good based on indicators comparison of FoodSCOR card. The added value shows a positive value, meaning that kelanting agroindustry is feasible to be developed. Key words: added value, kelanting, supply chain.